Detection of proteoglycan loss from articular cartilage using Brillouin microscopy, with applications to osteoarthritis - Wu, Pei-Jung (2019)
The degeneration of articular cartilage (AC) occurs in osteoarthritis (OA), which is a leading cause of pain and disability in middle-aged and older people. The early disease-related changes in cartilage extra-cellular matrix (ECM) start with depletion of proteoglycan (PG), leading to an increase in tissue hydration and permeability. These early compositional changes are small (<10%) and hence difficult to register with conventional non-invasive imaging technologies (magnetic resonance and ultrasound imaging). Here we apply Brillouin microscopy for detecting changes in the mechanical properties and composition of porcine AC. OA-like degradation is mimicked by enzymatic tissue digestion, and we compare Brillouin microscopy measurements against histological staining of PG depletion over varying digestion times and enzyme concentrations. The non-destructive nature of Brillouin imaging technology opens new avenues for creating minimally invasive arthroscopic devices for OA diagnostics and therapeutic monitoring.